2008
DOI: 10.1111/j.1742-4658.2008.06541.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of berberine to human telomeric quadruplex – spectroscopic, calorimetric and molecular modeling studies

Abstract: This study examines the characteristics of binding of berberine to the human telomeric d[AG3(T2AG3)3] quadruplex. By employing UV‐visible spectroscopy, fluorescence spectroscopy and isothermal titration calorimetry, we found that the binding affinity of berberine to the human telomeric quadruplex is 106. The complete thermodynamic profile for berberine binding to the quadruplex, at 25 °C, shows a small negative enthalpy (ΔH) of −1.7 kcal·mol−1, an entropy change with TΔS of +6.5 kcal·mol−1, and an overall favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 60 publications
10
93
1
Order By: Relevance
“…This unique activity of telomerase makes the enzyme an ideal probe for tumor diagnosis and a target for cancer chemotherapy [8,9]. Molecules, which have (a) a π-delocalized system, (b) a partial positive charge in the center of the molecular scaffold, and (c) a positively charged substituent to interact with the grooves, loops, and the negatively charged phosphate backbone, most likely interact with and further stabilize G-quadruplexes [10]. Therefore, many research groups have designed and synthesized some molecules with such structures, which are believed to be able to interact with G-quadruplex DNA structures.…”
Section: Introductionmentioning
confidence: 99%
“…This unique activity of telomerase makes the enzyme an ideal probe for tumor diagnosis and a target for cancer chemotherapy [8,9]. Molecules, which have (a) a π-delocalized system, (b) a partial positive charge in the center of the molecular scaffold, and (c) a positively charged substituent to interact with the grooves, loops, and the negatively charged phosphate backbone, most likely interact with and further stabilize G-quadruplexes [10]. Therefore, many research groups have designed and synthesized some molecules with such structures, which are believed to be able to interact with G-quadruplex DNA structures.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of hypochromicity observed here (>38.2%) is consistent with ligands such as TmPyP4 that can interact with the K+ 22mer by both end-stacking and intercalation [132]. However, intercalation of ligands such as TmPyP4 is typically characterized by a bathochromic, red shift of> 15 nm, while reports for ligands that interact by end-stacking such as Berberine are in the range of 8 -12 nm [132,146,203,209,215]. Additionally, it has been reported that intercalation is energetically less favorable than terminal end-stacking due to the challenge of quadruplexes accommodating ligands stacked between existing guanine quartets [209].…”
Section: Virtual Screening Discovery Of a Novelsupporting
confidence: 84%
“…In this class of compounds, the side chains are non-aromatic (Figure 57). Berberine has been shown to bind to predominantly triplex and quadruplex nucleic acids by intercalation or end-stacking [112,[145][146][147]. A preference for AT base pairs is notable for berberine [147].…”
Section: Cyclic Aromatic Derivatives This Group Of Compounds Along mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Mulholland and Wu employed the GAFF and parmbsc0 force fields to systematically explore the binding of telomestatin to human telomeric DNA. 99 More recently, combined experimental and computational methods 100 have been used to investigate the interactions between the isoquinoline alkaloid ligands and a 3 + 1 hybrid-type human telomeric quadruplex structure (PDB id 2MB3). 47 In this study, Noureini et al docked the ligands using the ICM-Pro MolSoft molecular modelling suite.…”
Section: Automated Molecular Dockingmentioning
confidence: 99%